Flood Prone Mapping based on Surface Runoff Analysis using the SWAT Model at the Upstream Side of Brantas - Nurcahyaningtyas, Devi; Harisuseno, Donny; Fidari, Jadfan Sidqi (Fakultas Teknik, Universitas Brawijaya, 2024)
Currently, Batu City is experiencing rapid development both in terms of population and the amount of land building. Where development is uncontrolled and not balanced by reasonable conservation efforts, it will cause water resource problems such as flooding. So, it is necessary to understand flow patterns better as an actual effort in effective water management and flood hazard mitigation. This study aims to obtain a map of flood-prone areas in the Brantas sub-watershed upstream of Batu City. The primary methodology adopted in this research entails the examination of surface runoff through the utilization of the ArcSWAT program, followed by the analysis of pertinent parameters, including rainfall, land use, soil type, land slope, river density, and surface runoff. Then, scoring and weighting are done before overlaying each parameter to get a flood vulnerability map at the research location. The results of this study indicate that the mapping of flood-prone areas at the most significant research location is at a high level of flood vulnerability of 78.31 km2 or 52.22% of the total area of the watershed.